SEM Investigation of Pollen Taxa in Honeys from Autochtone Apis cerana in Godavari, Lalitpur District, Nepal - Paudayal, Khum Narayan; Gautam, Ishan (Journal of Natural History Museum, 2015)
Pollen analysis of 8 multifloral honey samples collected from 4 locations of Godavari, Lalitpur district, Nepal was performed using Scanning Electron Microscope (SEM). In this investigation, a wide range of foraging plant sources for Apis cerana honey bees was identified which demonstrates the adequate potential for expanding and sustaining beekeeping in this area. The palynological assemblage of a total of 44 species of pollen flora representing 28 families was identified to the generic and some up to species level. Some of the pollen grains identified to only families, belong to Acanthaceae, Apiaceae, Araliaceae, Chenopodiaceae, Compositae, Lamiaceae, Loranthaceae, Meliaceae, Poaceae, Rosaceae, Rutaceae and Pteridaceae. The pollen assemblages in honeys were mostly belonging to angiosperms while the gymnosperm pollen was completely absent. One pteridophyte spore belonging to family Pteridaceae recovered. In this paper the morphology of the pollen grains based on SEM observation are described and the importance of the systematic documentation of various bee flora are discussed. J. Nat. Hist. Mus. Vol. 26, 2012: 29-67